(untitled) (Historia, 2021)
Dutch emigrants on the farm Wonderfontein, 1928-1969: a successful failure under the banner of kinsman relations and economic motives The Wonderfontein immigration project in South Africa by the Dutch related company ZASM can be interpreted as a success or a failure - depending on the way the history of the Wonderfontein project is approached. Perhaps a failure regarding the original aim of developing an agricultural oriented community and economy. By being "involved" in Wonderfontein the financial outcome for the ZASM appears to have been a raving success because of the profits they made from selling land they obtained for much less. It is unlikely that a notion of preserving a kinsman relation played an important part in any vision or political motive that might have existed with Dutch or South African leaders or even the ZASM executive. Individual motives through the decades since Dutch settlement in Wonderfontein (Carletonville) in 1928, directed the degree of involvement. Financial enthusiasm was a key word in every aspect of Wonderfontein involvement up until the selling of the outstanding property in 1969.